Analysis of Influencing Generation Z Purchasing Decisions in East Java Through Electronic Word of Mouth (E-WOM) Mediation - Debby Yunitasari; Fahrurrozi Fahrurrozi; Muhammad Isbad Addainuri (Bina Nusantara University, 2025)
Generation Z spends more time on social media than on television, making their purchasing decisions influenced by digital content. The research attempted to analyze the factors of consumer behavior with a focus on their impact on Generation Z’s purchasing decisions. In addition, researchers examined the mediation relationship between the factors of purchasing decisions with electronic Word of Mouth (e-WOM). The research aimed to analyze the factors that influence Generation Z’s purchasing decisions at TikTok Shop, focusing on the role of influencer marketing, Fear of Missing Out (FOMO), and hedonic motivation through the mediation of e-WOM on purchasing decisions. The research uses a quantitative approach by collecting data from 260 respondents through a purposive sampling method. Data were obtained through an online questionnaire with a Likert scale, analyzed using SEM-PLS version 4.0. The results show that influencer marketing, FOMO, hedonic motivation, and e-WOM have a positive and significant effect on purchasing decisions. E-WOM significanty mediates the influence of influencer marketing and hedonic motivation on purchasing decisions, but does not mediate the influence of FOMO. Purchasing decisions are enhanced through the optimization of influencer marketing, the increased role of e-WOM as a communication strategy, and campaigns that evoke hedonistic motivation and FOMO. Researchers and practitioners can also leverage TikTok Shop as a strategic channel to quickly understand market responses. Businesses can also integrate emotional elements (hedonistic motivation and FOMO) and social elements (e-WOM and influencer marketing) into their digital marketing efforts to enhance product appeal.